Bridging Budgeting and Well-Being: The Strategic Role of Self-Control in Financial Behavior - Rosananda Oktala; Ewirta Lista Pertaviana (Department of Business Administration Politeknik Negeri Sriwijaya, 2026)
This study investigates the influence of financial budgeting on financial well-being and examines the moderating role of self-control among employees of Bank Pembangunan Daerah (BPD) Sumsel in Indonesia. Using a quantitative approach, data were collected from 160 respondents and analyzed through Structural Equation Modeling with SmartPLS 4.0. The results reveal that financial budgeting significantly enhances financial well-being (β = 0.432, p < 0.001), suggesting that individuals who actively plan and manage their finances experience greater financial satisfaction and security. Furthermore, self-control significantly moderates this relationship, indicating that individuals with higher self-control are more capable of converting financial plans into consistent behavior, thus amplifying the positive effects of budgeting on well-being. These findings underscore the importance of integrating psychological dimensions into financial literacy programs. Financial interventions that combine budgeting education with self-control strengthening tools—such as behavioral coaching, commitment devices, or digital nudges—are likely to yield more sustainable improvements in financial well-being. This study contributes to the literature by positioning self-control not only as a personal trait but also as a strategic enabler that bridges the gap between financial planning and financial outcomes, particularly in the context of salaried professionals in emerging economies.